Preparation method of boron-doped modified silicon composite negative electrode material
Through the preparation method of boron-doped modified silicon composite negative electrode material, the composite of boron-doped silicon nanowires and multi-layer MXene material is solved, and the capacity attenuation problem caused by volume expansion during charge and discharge of silicon-based negative electrode material is achieved, achieving higher cycling performance and conductivity.
Patent Information
- Application Number
- CN202510039914.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The silicon-based negative electrode material produces large volume expansion and contraction during charging and discharging, resulting in a rapid attenuation of the capacity of the negative electrode material.
Boron-doped modified silicon composite negative electrode material is prepared by the template method and ultra-vacuum CVD deposition technology, and is combined with multi-layer MXene material to enhance conductivity and diffusion rate of lithium ions while providing a containment space to alleviate volume expansion.
It effectively reduces the volume expansion rate of the negative electrode material during the cycle charging and discharging process, improves the cyclic performance and conductivity of the negative electrode material, and extends the service life of the battery.
Smart Images

Figure CN119852362A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of battery negative electrode materials, and in particular to a method for preparing a boron-doped modified silicon composite negative electrode material. Background Art
[0002] Silicon-based negative electrodes have attracted much attention due to their high theoretical specific capacity (~4212 mAh / g). As a material that can form alloys with lithium, each silicon atom can react with 4.4 lithium ions, which is a huge improvement over the capacity of commercial graphite (~372 mAh / g). This makes it regarded as the next generation of negative electrode materials. At the same time, silicon is one of the most abundant elements on Earth, and its low cost is also one of the reasons why it has attracted attention.
[0003] However, silicon-based negative electrode materials will produce large volume expansion and contraction during the charging and discharging process. Multiple volume expansion and contraction will cause the negative electrode material to fall off, resulting in a rapid decrease in the capacity of the negative electrode material. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a boron-doped modified silicon composite negative electrode material, which solves the technical problem that silicon-based negative electrode materials produce large volume expansion and contraction during the charge and discharge process, thereby causing the negative electrode material capacity to decay rapidly.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] The present invention provides a method for preparing a boron-doped modified silicon composite negative electrode material, comprising the following steps:
[0009] S1. Preparation of Boron-doped Silicon Nanowires
[0010] S11, providing a silicon substrate, and after cleaning, using aluminum as a plating source to form an aluminum film with a thickness of 5 to 20 μm on the surface of the silicon substrate to obtain an aluminum film-modified silicon substrate;
[0011] S12, forming pores in the aluminum film modified silicon substrate to prepare a porous aluminum oxide film modified silicon substrate;
[0012] S13, depositing an Au (gold) layer on the surface of the porous aluminum oxide film modified silicon substrate to obtain a gold layer porous aluminum oxide film modified silicon substrate, and then co-depositing on the gold layer porous aluminum oxide film modified silicon substrate using silane, borane and hydrogen as reaction gases, and acid washing after deposition to obtain a boron-doped silicon nanowire array;
[0013] S2. preparing a multilayer MXene material, wherein the size of the multilayer MXene is 5 μm to 10 μm;
[0014] S3. Dispersing the boron-doped silicon nanowire material and the multilayer MXene material in a solvent, and performing ultra-low temperature freeze-drying on the resulting solution at -100°C to -50°C to obtain a boron-doped silicon nanowire / multilayer MXene composite negative electrode material.
[0015] In the preparation method of boron-doped modified silicon composite negative electrode material, boron doping can increase the intrinsic conductivity of silicon materials, improve the atomic mixing degree in silicon-based unit cells, and reduce the volume expansion rate of negative electrode materials during cyclic charge and discharge. At the same time, the coating of boron elements can effectively isolate the direct contact between silicon powder particles and electrolyte, avoid the generation of side reactions and the consumption of electrolyte. MXene materials improve the conductivity of negative electrode materials and the diffusion rate of lithium ions, thereby reducing the polarization of electrodes. At the same time, its open structure provides accommodation space for the volume expansion of negative electrode materials, avoiding the volume expansion of negative electrode materials causing the negative electrode materials to fall off, thereby improving the cycle performance of negative electrode materials.
[0016] Preferably, the pore formation in S12 includes the following steps: placing the aluminum film modified silicon substrate in an electrolyte, controlling the constant voltage to 1-20V and the constant current to 0.3-2.5A to form pores on the aluminum film modified silicon substrate by anodization to form a porous aluminum oxide film modified silicon substrate with a pore size of 100-300nm.
[0017] Preferably, the electrolyte comprises an acid and a solvent, the acid is selected from one or both of concentrated phosphoric acid and oxalic acid, and the solvent is selected from at least one of ethanol, ethylene glycol and deionized water.
[0018] Preferably, the pore-forming process further includes polishing the aluminum film-modified silicon substrate before the pore-forming process, which specifically includes the following steps:
[0019] The aluminum film is removed to modify the oxide layer on the surface of the silicon substrate, and then the current density is 50 to 200 mA cm -2 , the aluminum film modified silicon substrate is electrochemically polished under the conditions of a polishing time of 50 to 100 seconds to obtain a polished aluminum film modified silicon substrate, the electrochemical polishing electrolyte includes phosphoric acid, chromium trioxide, and water, and the mass ratio of the phosphoric acid, chromium trioxide, and water is 80:5 to 12:8 to 15.
[0020] Preferably, the aluminum film modified silicon substrate is placed in a sodium hydroxide solution to remove the surface oxide layer, the sodium hydroxide solution has a concentration of 0.02wt% to 10wt% and a temperature of 50 to 80°C.
[0021] Preferably, the co-deposition in S13 comprises the following steps:
[0022] Under protective atmosphere conditions, the borane, silane and hydrogen are co-deposited at a gas flow ratio of 0.5-5:60:1-5, the deposition temperature is 500° C.-1000° C., the deposition time is 1-5 hours, and the protective atmosphere is selected from one of nitrogen, argon or argon-hydrogen mixed gas.
[0023] Preferably, in S13, the pickling acid is selected from one or two of dilute hydrochloric acid, dilute sulfuric acid and dilute nitric acid.
[0024] Preferably, in S11, the silicon substrate is cleaned with acetone, ethanol, hydrofluoric acid and deionized water ultrasonically for 15 to 20 minutes in sequence to preliminarily remove organic and inorganic impurities, and then dried at 50 to 70° C., and then aluminum is used as a plating source to form an aluminum film on the surface of the silicon substrate.
[0025] Preferably, S2 comprises the following steps: preparing a multilayer MXene material by a hydrofluoric acid etching method, the etching temperature is 45° C. to 80° C., the hydrofluoric acid concentration is 10% to 20%, and the etching time is 36 h to 72 h.
[0026] Preferably, the solvent in S3 is selected from any one of ethanol, ethylene glycol and propanol.
[0027] Preferably, S3 satisfies at least one of the following conditions:
[0028] The mass ratio of boron-doped silicon nanowire material and multilayer MXene material is 5:0.5-2;
[0029] The mass volume ratio of the total mass of the boron-doped silicon nanowire material and the multilayer MXene material to the solvent is 1:3-10. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is the SEM spectrum of the boron-doped silicon nanowire / multilayer MXene composite negative electrode material prepared in Example 1;
[0032] Figure 2 SEM images of the pore structure of the porous alumina film modified with silicon substrate prepared under different voltages;
[0033] Among them, (a) is 10V and (b) is 4V. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The embodiment of the present application provides a method for preparing a boron-doped modified silicon composite negative electrode material, thereby solving the technical problem that silicon-based negative electrode materials produce large volume expansion and contraction during the charge and discharge process, thereby causing the negative electrode material capacity to decay rapidly.
[0036] The technical solution in the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:
[0037] The purpose of the present invention is to provide a method for preparing a boron-doped modified silicon composite negative electrode material, wherein boron-doped silicon nanowires are prepared by a template method and ultra-vacuum CVD deposition technology, and multilayer MXene is prepared by hydrogen fluoride (HF) wet etching, and a silicon nanowire / multilayer MXene negative electrode material is prepared after mixing.
[0038] The silicon wafer substrate is used as the raw material source of silicon nanowires. The silicon wafer is cleaned by the RCA method and then etched to obtain silicon nanowires. An aluminum film of a certain thickness is deposited on the surface of the silicon substrate by electron beam evaporation technology, and then the aluminum film is subjected to surface oxide treatment and electrochemical polishing. The polished aluminum film-modified silicon substrate is subjected to anodization to prepare an aluminum film with a pore structure. Finally, the porous aluminum oxide film-modified silicon substrate containing a nanoporous structure is placed in an ultra-vacuum CVD furnace for vapor phase co-deposition of silane and borane. Finally, the porous aluminum oxide film on the silicon composite substrate containing the boron-coated silicon nanowire material is pickled to obtain a boron-doped silicon nanowire array.
[0039] The MXene precursor is etched, and the etching solution is hydrochloric acid, hydrofluoric acid, etc., preferably hydrofluoric acid. The MXene precursor is placed in a heated hydrofluoric acid solution and then etched at a high temperature. After etching, the acid is removed until the solution is neutral, and filtered to obtain a MXene with an open structure. The MXene is stirred and mixed with boron-doped silicon nanowires to obtain a boron-doped silicon nanowire / multilayer MXene composite negative electrode material, which is coated, dried, sliced, and placed in a glove box for half-battery assembly using a CR2032 battery shell. The battery cycle performance test uses the Newwell BST3000 test system, and the above tests are all carried out at room temperature.
[0040] Compared with other silicon negative electrode preparation methods, this method can better control the size of silicon nanowires and their growth direction. At the same time, the use of boron for doping can increase the intrinsic conductivity of silicon-based negative electrode materials, improve the mixing degree of atoms in silicon-based unit cells, and reduce the expansion rate of materials during cyclic charge and discharge. The doping and coating of boron can effectively isolate the direct contact between silicon powder particles and electrolyte, avoid the generation of side reactions and the consumption of electrolyte. However, due to the poor conductivity of silicon materials, it is difficult to obtain certain applications in rate performance. Therefore, MXene materials with high conductivity can be very suitable for semiconductor silicon negative electrodes, which can effectively improve the conductivity of materials. At the same time, MXene greatly improves the diffusion rate of lithium ions and reduces the polarization of electrodes. At the same time, its open structure is very suitable for the expansion and contraction of silicon negative electrodes, improving cycle performance. In order to adapt to the development of the next generation of silicon-based negative electrode materials and further reduce costs, the high nano-, high conductivity and high performance of silicon nanowire negative electrodes are one of the inevitable development directions of the next generation of silicon-based negative electrode materials.
[0041] There are a lot of structural gaps between the nanowires, which can well accommodate the volume changes caused by the negative electrode material during the charging and discharging process, thereby reducing the internal stress accumulation on the electrode surface and the risk of electrode breakage. It is more conducive to the further industrial production and commercialization of silicon negative electrodes.
[0042] The preparation method of the boron-doped modified silicon composite negative electrode material of the present application uses a template-co-deposition method to prepare silicon nanowires. First, a porous oxide template is prepared by an anodic oxidation method, and then silicon nanowires are prepared by the template. Borane is co-deposited during the growth of the silicon nanowires to change the atomic ordering structure inside the silicon-based nanowires. At the same time, the surface of the silicon nanowires is modified by boron. Then, the prepared silicon nanowire material is compositely blended with a MXene material to obtain a boron-doped modified silicon composite negative electrode material.
[0043] The equipment of this application is relatively simple and the preparation is fast. The material has the characteristics of controllable size and excellent cycle performance. This provides a more reliable solution for the next generation of silicon-based negative electrodes with high nano-size, high conductivity and high performance.
[0044] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0045] Example 1
[0046] This embodiment provides a method for preparing a boron-doped modified silicon composite negative electrode material, comprising the following steps:
[0047] S1. Preparation of Boron-doped Silicon Nanowires
[0048] S11. Use acetone, anhydrous ethanol, hydrofluoric acid, and deionized water to ultrasonically clean for 20 minutes in sequence to remove organic and inorganic impurities on the surface of the silicon wafer. Place the cleaned silicon wafer in a blast drying oven and dry it at 60°C. Then, use an aluminum block as an evaporation source to evaporate an aluminum film with a thickness of 10 μm on the surface of the silicon wafer by electron beam evaporation to prepare an aluminum film modified silicon substrate. The evaporation time is 5 hours.
[0049] S12, placing the obtained aluminum film modified silicon substrate into a 2 wt % sodium hydroxide solution, and washing it at 60° C. for 2 min to remove the aluminum oxide impurity layer on the surface.
[0050] S13, electrochemical polishing of the aluminum film modified silicon substrate with the surface oxide layer removed, using an electrolyte composed of phosphoric acid, chromium trioxide, and water at 120 mA cm -2 The aluminum foil surface is polished by constant current electrochemical polishing at a current density of , so that the surface of the aluminum foil becomes a bright mirror surface, and a polished aluminum film modified silicon substrate is obtained. Since the aluminum film in S12 is cleaned with alkali solution, there will be defects on the surface. The polishing treatment can remove these defects and make the subsequent reaction more uniform. Then the polished aluminum film modified silicon substrate is washed with deionized water and dried for use. The mass ratio of phosphoric acid, chromium trioxide and water is 80:12:8, and the polishing time is 50s.
[0051] S14. Place the polished aluminum film modified silicon substrate in a 6wt% phosphoric acid solution with ethylene glycol and deionized water as solvents, control the constant voltage to 6V, and make holes on the polished aluminum film by anodization to form a porous aluminum oxide film modified silicon substrate with a pore size of 100nm. Among them, the porous aluminum oxide film is the template for preparing nanowires in the next step, that is, a porous oxide template is prepared by anodization. The porous aluminum oxide template is easier to remove in the later stage. Due to the intrinsic expansion problem of silicon negative electrode materials, which will cause particle breakage, the reserved pore size of the porous aluminum oxide template can buffer the particle fragmentation caused by the expansion of silicon lithium insertion process, thereby inhibiting the formation of SEI and reducing the consumption of electrolyte. If the pore size is too small, the reserved buffer pore size is insufficient and the expansion cannot be effectively alleviated.
[0052] S15. After cleaning the porous alumina film modified silicon substrate with HF aqueous solution, electron-free deposition is performed to deposit a layer of Au on the porous alumina film surface of the porous alumina film modified silicon substrate to obtain a gold layer porous alumina film modified silicon substrate, and the gold layer porous alumina film modified silicon substrate is placed in an etching solution containing H2O2 and HF for etching to obtain silicon nanowires.
[0053] Among them, the mechanism of depositing the Au layer is that a large number of Si-H bonds are formed on the surface of the silicon wafer exposed at the pores of the porous alumina membrane after HF treatment. The Si-H bond has a strong reducing property, and Au+ has a strong oxidizing property. The two undergo an oxidation-reduction reaction, and Au+ obtains electrons and is reduced to Au atoms and is deposited on the Si surface in the form of nanoparticles to form a discontinuous Au particle film.
[0054] In addition, the etching mechanism is that the Au particles act as catalysts, and the Si below the Au particles is oxidized to SiO2 by the H2O2 in the etching solution and dissolved by HF, causing the Au particles to sink. Therefore, the Si at the position covered by the Au particles is gradually etched downward to form "tunnels". Since the Au particle film is discontinuous, the gaps between adjacent Au particles are not etched, resulting in the formation of silicon nanowires between adjacent "tunnels".
[0055] The reaction formula is as follows:
[0056] Si+2H2O2+6F - +4H + →[SiF6] 2- +4H2O.
[0057] S16, transferring the gold layer porous alumina film modified silicon substrate to the PECVD preparation chamber, drawing a vacuum in the furnace chamber, using silane, borane and hydrogen as reaction gases, and sequentially performing primary reaction and secondary reaction for deposition. During the deposition process, the silane flow rate is 6 sccm, the borane flow rate is 0.7 sccm, and the hydrogen flow rate is 160 sccm. After deposition, a certain amount of boron is deposited between the silicon nanowires, and the silicon nanowires coated with boron are obtained by cooling.
[0058] Among them, the primary reaction and the secondary reaction occur in sequence for deposition. The primary reaction is that silane and borane are hit by electrons to produce ionic groups (silicon ions, boron ions, hydrogen ions) and neutral groups (hydrogen). The secondary reaction is that the generated ionic groups collide with the neutral groups to form new groups (silicon element, boron element, hydrogen), which are the raw materials for the deposition of nano-silicon particles. The obtained new groups are deposited in the pores of the porous alumina template to form silicon nanowires, changing the atomic arrangement structure inside the silicon-based nanowires, and at the same time, the surface of the silicon nanowires is modified by boron, so as to obtain a porous alumina film-modified silicon nanowire array template for depositing silicon nanowires.
[0059] S17, washing the silicon nanowire array template modified with the porous alumina film on which the silicon nanowires are deposited with acid with 5wt% dilute hydrochloric acid to remove the surface-modified porous alumina film, and then washing with deionized water to obtain a boron-doped silicon nanowire array.
[0060] S2. Preparation of multilayer MXene
[0061] Prepare a hydrofluoric acid etching solution with a concentration of 5%, place the MXene precursor pure silicon material in the etching solution at 45°C and etch for 54 hours, collect the MXene, adjust the pH of the collected MXene to neutral, and then filter and collect to obtain multilayer MXene.
[0062] S3. Preparation of Boron-doped Silicon Nanowire / Multilayer MXene Composite Anode Materials
[0063] Boron-doped silicon nanowires and multilayer MXene materials are mixed in a mass ratio of 5:0.5 and dispersed in ethanol under ultrasonic action. The mass volume ratio of the total mass of the boron-doped silicon nanowire material and the multilayer MXene material to the mass volume ratio of ethanol is 1:3. The obtained solution is ultra-low temperature freeze-dried and crushed at -100°C to obtain a boron-doped silicon nanowire / multilayer MXene composite negative electrode material.
[0064] According to the ratio of boron-doped silicon nanowire / multilayer MXene composite negative electrode material: binder: conductive agent = 8:1:1, a boron-doped modified silicon composite negative electrode slurry was prepared, the prepared negative electrode slurry was coated and sliced, and then sliced into discs with a diameter of 14 mm, and placed in a glove box with a water and oxygen concentration of less than 0.1 ppm. A half-cell with a lithium sheet as the counter electrode was prepared using a CR2032 battery shell. The prepared half-cell was placed for more than 10 hours to ensure sufficient immersion of the electrolyte, and the half-cell was subjected to battery charge and discharge tests. The test results are shown in Table 1.
[0065] Example 2
[0066] This embodiment provides a method for preparing a boron-doped modified silicon composite negative electrode material, comprising the following steps:
[0067] S1. Preparation of Boron-doped Silicon Nanowires
[0068] S11. Use acetone, anhydrous ethanol, hydrofluoric acid, and deionized water to ultrasonically clean for 20 minutes in sequence to remove organic and inorganic impurities on the surface of the silicon wafer. Place the cleaned silicon wafer in a blast drying oven and dry it at 60°C. Then, use an aluminum block as an evaporation source to evaporate an aluminum film with a thickness of 10 μm on the surface of the silicon wafer by electron beam evaporation to prepare an aluminum film modified silicon substrate. The evaporation time is 5 hours.
[0069] S12, placing the obtained aluminum film modified silicon substrate into a 2 wt % sodium hydroxide solution, and washing it at 60° C. for 2 min to remove the aluminum oxide impurity layer on the surface.
[0070] S13, electrochemical polishing of the aluminum film modified silicon substrate with the surface oxide layer removed, using an electrolyte composed of phosphoric acid, chromium trioxide, and water at 120 mA cm -2The aluminum foil surface is polished by constant current electrochemical polishing at a current density of , so that the surface of the aluminum foil becomes a bright mirror surface, and a polished aluminum film modified silicon substrate is obtained. Since the aluminum film in S12 is cleaned with alkali solution, there will be defects on the surface. The polishing treatment can remove these defects and make the subsequent reaction more uniform. Then the polished aluminum film modified silicon substrate is washed with deionized water and dried for use. The mass ratio of phosphoric acid, chromium trioxide and water is 80:12:8, and the polishing time is 70s.
[0071] S14. Place the polished aluminum film modified silicon substrate in a 6wt% phosphoric acid solution with ethylene glycol and deionized water as solvents, control the constant voltage to 6V, and make holes on the polished aluminum film by anodization to form a porous aluminum oxide film modified silicon substrate with a pore size of 100nm. Among them, the porous aluminum oxide film is the template for preparing nanowires in the next step, that is, a porous oxide template is prepared by anodization. The porous aluminum oxide template is easier to remove in the later stage. Due to the intrinsic expansion problem of silicon negative electrode materials, which will cause particle breakage, the reserved pore size of the porous aluminum oxide template can buffer the particle fragmentation caused by the expansion of silicon lithium insertion process, thereby inhibiting the formation of SEI and reducing the consumption of electrolyte. If the pore size is too small, the reserved buffer pore size is insufficient and the expansion cannot be effectively alleviated.
[0072] S15. After cleaning the porous alumina film modified silicon substrate with HF aqueous solution, electron-free deposition is performed to deposit a layer of Au on the porous alumina film surface of the porous alumina film modified silicon substrate to obtain a gold layer porous alumina film modified silicon substrate, and the gold layer porous alumina film modified silicon substrate is placed in an etching solution containing H2O2 and HF for etching to obtain silicon nanowires.
[0073] Among them, the mechanism of depositing the Au layer is that a large number of Si-H bonds are formed on the surface of the silicon wafer exposed at the pores of the porous alumina membrane after HF treatment. The Si-H bond has a strong reducing property, and Au+ has a strong oxidizing property. The two undergo an oxidation-reduction reaction, and Au+ obtains electrons and is reduced to Au atoms and deposited on the Si surface in the form of nanoparticles to form a discontinuous Au particle film.
[0074] In addition, the etching mechanism is that the Au particles act as catalysts, and the Si below the Au particles is oxidized to SiO2 by the H2O2 in the etching solution and dissolved by HF, causing the Au particles to sink. Therefore, the Si at the position covered by the Au particles is gradually etched downward to form "tunnels". Since the Au particle film is discontinuous, the gaps between adjacent Au particles are not etched, resulting in the formation of silicon nanowires between adjacent "tunnels".
[0075] S16, transferring the gold layer porous alumina film modified silicon substrate to the PECVD preparation chamber, drawing a vacuum in the furnace chamber, using silane, borane and hydrogen as reaction gases, and sequentially performing primary reaction and secondary reaction for deposition. During the deposition process, the silane flow rate is 6 sccm, the borane flow rate is 0.7 sccm, and the hydrogen flow rate is 160 sccm. After deposition, a certain amount of boron is deposited between the silicon nanowires, and the silicon nanowires coated with boron are obtained by cooling.
[0076] Among them, the primary reaction and the secondary reaction occur in sequence for deposition. The primary reaction is that silane and borane are hit by electrons to produce ionic groups (silicon ions, boron ions, hydrogen ions) and neutral groups (hydrogen). The secondary reaction is that the generated ionic groups collide with the neutral groups to form new groups (silicon element, boron element, hydrogen), which are the raw materials for the deposition of nano-silicon particles. The obtained new groups are deposited in the pores of the porous alumina template to form silicon nanowires, changing the atomic arrangement structure inside the silicon-based nanowires, and at the same time, the surface of the silicon nanowires is modified by boron, so as to obtain a porous alumina film-modified silicon nanowire array template for depositing silicon nanowires.
[0077] S17, washing the silicon nanowire array template modified with the porous alumina film on which the silicon nanowires are deposited with acid with 5wt% dilute hydrochloric acid to remove the surface-modified porous alumina film, and then washing with deionized water to obtain a boron-doped silicon nanowire array.
[0078] S2. Preparation of multilayer MXene
[0079] Prepare a hydrofluoric acid etching solution with a concentration of 5%, place the MXene precursor pure silicon material in the etching solution at 45°C and etch for 54 hours, collect the MXene, adjust the pH of the collected MXene to neutral, and then filter and collect to obtain multilayer MXene.
[0080] S3. Preparation of Boron-doped Silicon Nanowire / Multilayer MXene Composite Anode Materials
[0081] Boron-doped silicon nanowires and multilayer MXene materials are mixed in a mass ratio of 5:1 and dispersed in ethylene glycol under ultrasonic action. The mass volume ratio of the total mass of the boron-doped silicon nanowire material and the multilayer MXene material to the ethylene glycol is 1:6. The obtained solution is ultra-low temperature freeze-dried and crushed at -70°C to obtain a boron-doped silicon nanowire / multilayer MXene composite negative electrode material.
[0082] According to the ratio of boron-doped silicon nanowire / multilayer MXene composite negative electrode material: binder: conductive agent = 8:1:1, a boron-doped modified silicon composite negative electrode slurry was prepared, the prepared negative electrode slurry was coated and sliced, and then sliced into discs with a diameter of 14 mm, and placed in a glove box with a water and oxygen concentration of less than 0.1 ppm. A half-cell with a lithium sheet as the counter electrode was prepared using a CR2032 battery shell. The prepared half-cell was placed for more than 10 hours to ensure sufficient immersion of the electrolyte, and the half-cell was subjected to battery charge and discharge tests. The test results are shown in Table 1.
[0083] Example 3
[0084] This embodiment provides a method for preparing a boron-doped modified silicon composite negative electrode material, comprising the following steps:
[0085] S1. Preparation of Boron-doped Silicon Nanowires
[0086] S11. Use acetone, anhydrous ethanol, hydrofluoric acid, and deionized water to ultrasonically clean for 20 minutes in sequence to remove organic and inorganic impurities on the surface of the silicon wafer. Place the cleaned silicon wafer in a blast drying oven and dry it at 60°C. Then, use an aluminum block as an evaporation source to evaporate an aluminum film with a thickness of 10 μm on the surface of the silicon wafer by electron beam evaporation to prepare an aluminum film modified silicon substrate. The evaporation time is 5 hours.
[0087] S12, placing the obtained aluminum film modified silicon substrate into a 2 wt % sodium hydroxide solution, and washing it at 60° C. for 2 min to remove the aluminum oxide impurity layer on the surface.
[0088] S13, electrochemical polishing of the aluminum film modified silicon substrate with the surface oxide layer removed, using an electrolyte composed of phosphoric acid, chromium trioxide, and water at 120 mA cm -2 The aluminum foil surface is polished by constant current electrochemical polishing at a current density of , so that the surface of the aluminum foil becomes a bright mirror surface, and a polished aluminum film modified silicon substrate is obtained. Since the aluminum film in S12 is cleaned with alkali solution, there will be defects on the surface. The polishing treatment can remove these defects and make the subsequent reaction more uniform. Then the polished aluminum film modified silicon substrate is washed with deionized water and dried for standby use. The mass ratio of phosphoric acid, chromium trioxide and water is 80:12:8, and the polishing time is 100s.
[0089] S14. Place the polished aluminum film modified silicon substrate in a 6wt% phosphoric acid solution with ethylene glycol and deionized water as solvents, control the constant voltage to 6V, and make holes on the polished aluminum film by anodization to form a porous aluminum oxide film modified silicon substrate with a pore size of 100nm. Among them, the porous aluminum oxide film is the template for preparing nanowires in the next step, that is, a porous oxide template is prepared by anodization. The porous aluminum oxide template is easier to remove in the later stage. Due to the intrinsic expansion problem of silicon negative electrode materials, which will cause particle breakage, the reserved pore size of the porous aluminum oxide template can buffer the particle fragmentation caused by the expansion of silicon lithium insertion process, thereby inhibiting the formation of SEI and reducing the consumption of electrolyte. If the pore size is too small, the reserved buffer pore size is insufficient and the expansion cannot be effectively alleviated.
[0090] S15. After cleaning the porous alumina film modified silicon substrate with HF aqueous solution, electron-free deposition is performed to deposit a layer of Au on the porous alumina film surface of the porous alumina film modified silicon substrate to obtain a gold layer porous alumina film modified silicon substrate, and the gold layer porous alumina film modified silicon substrate is placed in an etching solution containing H2O2 and HF for etching to obtain silicon nanowires.
[0091] Among them, the mechanism of depositing the Au layer is that a large number of Si-H bonds are formed on the surface of the silicon wafer exposed at the pores of the porous alumina membrane after HF treatment. The Si-H bond has a strong reducing property, and Au+ has a strong oxidizing property. The two undergo an oxidation-reduction reaction, and Au+ obtains electrons and is reduced to Au atoms and deposited on the Si surface in the form of nanoparticles to form a discontinuous Au particle film.
[0092] In addition, the etching mechanism is that the Au particles act as catalysts, and the Si below the Au particles is oxidized to SiO2 by the H2O2 in the etching solution and dissolved by HF, causing the Au particles to sink. Therefore, the Si at the position covered by the Au particles is gradually etched downward to form "tunnels". Since the Au particle film is discontinuous, the gaps between adjacent Au particles are not etched, resulting in the formation of silicon nanowires between adjacent "tunnels".
[0093] S16, transferring the gold layer porous alumina film modified silicon substrate to the PECVD preparation chamber, drawing a vacuum in the furnace chamber, using silane, borane and hydrogen as reaction gases, and sequentially performing primary reaction and secondary reaction for deposition. During the deposition process, the silane flow rate is 6 sccm, the borane flow rate is 0.7 sccm, and the hydrogen flow rate is 160 sccm. After deposition, a certain amount of boron is deposited between the silicon nanowires, and the silicon nanowires coated with boron are obtained by cooling.
[0094] Among them, the primary reaction and the secondary reaction occur in sequence for deposition. The primary reaction is that silane and borane are hit by electrons to produce ionic groups (silicon ions, boron ions, hydrogen ions) and neutral groups (hydrogen). The secondary reaction is that the generated ionic groups collide with the neutral groups to form new groups (silicon element, boron element, hydrogen), which are the raw materials for the deposition of nano-silicon particles. The obtained new groups are deposited in the pores of the porous alumina template to form silicon nanowires, changing the atomic arrangement structure inside the silicon-based nanowires, and at the same time, the surface of the silicon nanowires is modified by boron, so as to obtain a porous alumina film-modified silicon nanowire array template for depositing silicon nanowires.
[0095] S17, washing the silicon nanowire array template modified with the porous alumina film on which the silicon nanowires are deposited with acid with 5wt% dilute hydrochloric acid to remove the surface-modified porous alumina film, and then washing with deionized water to obtain a boron-doped silicon nanowire array.
[0096] S2. Preparation of multilayer MXene
[0097] Prepare a hydrofluoric acid etching solution with a concentration of 5%, place the MXene precursor pure silicon material in the etching solution at 45°C and etch for 54 hours, collect the MXene, adjust the pH of the collected MXene to neutral, and then filter and collect to obtain multilayer MXene.
[0098] S3. Preparation of Boron-doped Silicon Nanowire / Multilayer MXene Composite Anode Materials
[0099] Boron-doped silicon nanowires and multilayer MXene materials are mixed in a mass ratio of 5:2 and dispersed in propanol under ultrasonic action. The mass volume ratio of the total mass of the boron-doped silicon nanowire material and the multilayer MXene material to the propanol is 1:10. The obtained solution is ultra-low temperature freeze-dried and crushed at -50°C to obtain a boron-doped silicon nanowire / multilayer MXene composite negative electrode material.
[0100] According to the ratio of boron-doped silicon nanowire / multilayer MXene composite negative electrode material: binder: conductive agent = 8:1:1, a boron-doped modified silicon composite negative electrode slurry was prepared, the prepared negative electrode slurry was coated and sliced, and then sliced into discs with a diameter of 14 mm, and placed in a glove box with a water and oxygen concentration of less than 0.1 ppm. A half-cell with a lithium sheet as the counter electrode was prepared using a CR2032 battery shell. The prepared half-cell was placed for more than 10 hours to ensure sufficient immersion of the electrolyte, and the half-cell was subjected to battery charge and discharge tests. The test results are shown in Table 1.
[0101] Comparative Example 1
[0102] The difference between this comparative example and Example 1 is that the reaction gas in step S16 does not include borane, and only silane and hydrogen are used as reaction gases, and the rest is the same as Example 1.
[0103] Comparative Example 2
[0104] The difference between this comparative example and Example 1 is that 3wt% phosphoric acid is used instead of 6wt% phosphoric acid in step S14, and the rest is the same as Example 1. As shown in Table 1, the concentration of phosphoric acid will affect the pore size of the porous alumina membrane. A decrease in the concentration will cause the pore size of the porous alumina membrane to decrease accordingly, thereby affecting the performance of the prepared half-cell.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 1 is that S2 and S3 are not included, and boron-doped silicon nanowires are used to replace boron-doped silicon nanowires / multilayer MXene composite negative electrode materials to prepare negative electrode slurry, and the rest is the same as Example 1. As can be seen from Table 1, multilayer MXene can effectively alleviate the expansion effect of silicon nanowire particles during the charging and discharging process, and avoid the active material in the battery cell pole piece from expanding and causing the active material and the current collector to fall off, resulting in the degradation of the cycle performance.
[0107] Comparative Example 4
[0108] The difference between this comparative example 4 and example 1 is that in S14, a constant voltage of 9V is used instead of 6V, and the rest is the same as example 1. As shown in Table 1, the pore size of the material increases after the voltage is increased, resulting in an increase in the diameter of the silicon nanowires, thereby affecting the performance of the prepared half-cell.
[0109] Table 1 Performance test results of half-cells prepared in Examples 1-3 and Comparative Examples 1-4
[0110]
[0111] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0112] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
[0113] The present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a boron-doped modified silicon composite negative electrode material, characterized in that: The steps include: A silicon substrate is provided, an aluminum film with a thickness of 5 to 20 μm is formed on the surface of the silicon substrate, and then pores are formed to prepare a porous aluminum oxide film-modified silicon substrate; a gold layer is deposited on the surface of the porous aluminum oxide film-modified silicon substrate, and then a silicon source, a boron source and hydrogen are used as reactants for co-deposition, and then acid washing is performed to obtain a boron-doped silicon nanowire array; a multilayer MXene material and the boron-doped silicon nanowire material are dispersed in a solvent, and ultra-low temperature freeze-dried at -100°C to -50°C are performed to obtain a boron-doped silicon nanowire / multilayer MXene composite negative electrode material.
2. The preparation method according to claim 1, characterized in that The pore making comprises the following steps: after cleaning the silicon substrate, using aluminum as a plating source to form an aluminum film with a thickness of 5 to 20 μm on the surface of the silicon substrate to obtain an aluminum film modified silicon substrate; placing the aluminum film modified silicon substrate in an electrolyte, controlling a constant voltage of 1 to 20 V and a constant current of 0.3 to 2.5 A to make pores on the aluminum film modified silicon substrate by anodizing to form a porous aluminum oxide film modified silicon substrate with a pore size of 100 to 300 nm.
3. The preparation method according to claim 2, characterized in that: The electrolyte comprises an acid and a solvent, wherein the acid is selected from one or both of concentrated phosphoric acid and oxalic acid, and the solvent is selected from at least one of ethanol, ethylene glycol and deionized water.
4. The preparation method according to claim 2, characterized in that: The pore forming process also includes polishing the aluminum film modified silicon substrate before the pore forming process, which specifically includes the following steps: The aluminum film is removed to modify the oxide layer on the surface of the silicon substrate, and then the current density is 50 to 200 mA cm -2 , the aluminum film modified silicon substrate is electrochemically polished under the conditions of a polishing time of 50 to 100 seconds to obtain a polished aluminum film modified silicon substrate, the electrochemical polishing electrolyte includes phosphoric acid, chromium trioxide, and water, and the mass ratio of the phosphoric acid, chromium trioxide, and water is 80:5 to 12:8 to 15.
5. The preparation method according to claim 4, characterized in that: The aluminum film modified silicon substrate is placed in a sodium hydroxide solution to remove the surface oxide layer, wherein the concentration of the sodium hydroxide solution is 0.02wt% to 10wt% and the temperature is 50 to 80°C.
6. The preparation method according to claim 1, characterized in that: The co-deposition comprises the following steps: co-depositing the boron source, silicon source and hydrogen at a gas flow ratio of 0.5-5:60:1-5 under protective atmosphere conditions, the deposition temperature is 500° C.-1000° C., and the deposition time is 1-5 hours; and / or, The protective atmosphere is selected from one of nitrogen, argon or argon-hydrogen mixed gas; and / or, The silicon source is silane, and the boron source is borane.
7. The preparation method according to claim 1, characterized in that: The pickling acid is selected from one or two of dilute hydrochloric acid, dilute sulfuric acid and dilute nitric acid.
8. The preparation method according to claim 1, characterized in that: The method for preparing the multilayer MXene material is as follows: the multilayer MXene material is prepared by a hydrofluoric acid etching method, the etching temperature is 45° C. to 80° C., the hydrofluoric acid concentration is 10% to 20%, the etching time is 36h to 72h, and the size of the multilayer MXene is 5μm to 10μm.
9. The preparation method according to claim 1, characterized in that: The solvent is selected from any one of ethanol, ethylene glycol and propanol.
10. The preparation method according to claim 1, characterized in that: The mass ratio of the boron-doped silicon nanowire material to the multilayer MXene material is 5:0.5-2; The mass volume ratio of the total mass of the boron-doped silicon nanowire material and the multilayer MXene material to the solvent is 1:3-10.
Citation Information
Patent Citations
Preparation method for orderly silicon nanowire array
CN103112819A
Boron-doped silicon carbon negative electrode material, preparation method thereof and lithium ion battery
CN117613225A
Preparation method of silicon nanowire / multilayer MXene negative electrode material
CN118173739A
Article comprising silicon nanowires on a metal substrate
US20130220821A1
Silicon negative electrode material, preparation method therefor, negative electrode sheet, and lithium ion battery
WO2023207996A1